Job Satisfaction of Non-Permanent Teachers in South Nias Amid Limitation - Yohanes Dakhi, Timotius Duha, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
Teachers in South Nias still adhere to their culture and customs. They really hope that they are given the opportunity to get permission to attend indigenous cultural and cultural events as part ofbalancing work and life.Most of the teachers in South Nias only have the status of non-permanent teachers, or volunteers, but they are very proud of being teachers even with a small salary. Participants in this study were 46 junior highpublic school teachers in remote villages. Data were analyzed by Partial Least Square method to test the mediation effect to determine the effect of exogenous constructs with endogenous constructs through mediating variables. The result showed that work life balance had a positive and significant influence on self-esteem and job satisfaction. Self-esteem has a positive and significant influence on job satisfaction. Moreover, the total effect of work life balance on job satisfaction increases after mediated by self-esteem.